Oxidative Degradation of Reactive Violet 1 Dye by Ultraviolet Radiation in Presence of Hydrogen Peroxide - Muneer1, Majid; A. Bhatti3, Ijaz; Aslam2, Nosheen; Asghar Jamal1, Muhammad; Zafar4, Muddassar; Kaleem Khosa1, Muhammad (Asian Journal of Chemistry, 2014)
Degradation of synthetic dye reactive violet 1 in aqueous media having concentrations 10-50 mg/L has been carried out by UV radiation in presence of H2O2. The change in colour intensity at lmax 545 nm and chemical oxygen demand reduction was examined to evaluate the decrease in organic matter. The decrease in colour intensity was found 18, 25 and 100 % while chemical oxygen demand reduction up to 15, 25 and 55 % when solutions were treated by UV, H2O2 and UV/H2O2, respectively. The radiolytic end products were identified by FTIR and GC-MS, which revealed that advanced oxidation process had achieved the complete mineralization. The effect of different operational parameters such as initial dye concentration, UV irradiation time and concentration of hydrogen peroxide on degradation efficiency has also been evaluated. This treatment can be extended to dye containing industrial wastewater.